Cholecystectomy with combined transvaginal and transumbilical approach – an attempt to assess nursing problems - Dykas, Magdalena; Wieczorek-Wójcik, Beata; Bugalska, Agnieszka (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
One of the most frequently performed surgical operations in the abdomen nowadays is the removal of the gallbladder. The tendency is to reduce the invasive aspect of surgical procedures. The latest challenge to traditional laparoscopic surgical procedures is to perform them through natural body orifices (NOTES). The dynamic development of minimally invasive surgical techniques leads to an analysis of their impact on nursing care in the preoperative period. The aim of this study is to examine nursing care in the era of minimally invasive surgery, using as an example patients undergoing cholecystectomy performed with access through the vagina and umbilicus. Method : An the analyses of the medical records from preoperative and postoperative care – case study. Surgery using natural orifice techniques would minimise nursing intervention and therefore also reduce the risk of infection in the preoperative and postoperative care. Surgical Nursing goes hand in hand with the idea of minimally invasive surgery.